The Existence of Cryptocurrency from the Perspective of Islamic Fiqh: A Legal Analysis of the Buying and Selling of Digital Assets - Ahmad Rehan (Al-Fiqh: Journal of Contemporary Islamic Law, 2025)
This study aims to analyse the legal status and permissibility of crypto asset trading from the perspective of muamalah jurisprudence, in light of the growing practice of blockchain-based digital transactions within Muslim communities. The research addresses legal questions related to the use of crypto assets as a medium of exchange or trade commodity under Islamic law. Utilising a qualitative approach through library research, the study examines the views of classical and contemporary scholars, as well as official fatwas on digital assets. The findings suggest that the legality of crypto asset trading remains subject to ijtihad (independent legal reasoning), with considerations based on factors such as benefits, system security, and contract transparency. Some scholars prohibit crypto trading due to concerns over gharar (ambiguity) and excessive speculation. In contrast, others permit it on the condition that crypto assets function as commodities rather than currency, and adhere to sharia principles, including clarity of the object, proper contractual elements, and compliance with contract requirements. The implications of this research emphasise the need for sharia-compliant regulations and education to guide the Muslim community in making informed decisions when investing and trading digital assets in line with Islamic muamalah principles.